Baseline assessment report for Resilient Nature-based Water Solutions pilot in Izbat Al-Hamra, Egypt - Belhaj Fraj, Makram; Fragaszy, Stephen; Abdelwahab, Noura; Maowod, G.; AbdelMegeed, A.; Elhariry, R. T.; Samarasekara, Vidhisha (International Water Management Institute, 2025)
This report presents the baseline assessment for the Resilient Nature-Based Water Solutions (RNBWS) pilot project in Izbat Al-Hamra, Beheira Governorate, Egypt that is implemented under the Al Murunah project funded by the UK Government and led by the International Water Management Institute (IWMI) in partnership with the International Union for Conservation of Nature (IUCN). The study analyses the biophysical, agricultural, socio-economic, and policy contexts of the area to guide the design and implementation of integrated, community-based interventions that enhance water security, agricultural productivity, and climate resilience.